Optimization of Spent Coffee Ground Extraction for Kombucha Production: Effect of Temperature on Fermentation Dynamics and Antioxidant Activity - Sri Hartini; Margareta Novian Cahyanti; Alifia Dewi Safira (The University of Lampung, 2025)
The valorization of agro-industrial waste into functional beverages offers a sustainable approach to food processing. This study aimed to optimize the extraction temperature of spent coffee grounds for kombucha production and to evaluate its impact on fermentation dynamics and antioxidant activity. Spent coffee grounds were extracted at three different temperatures (30°C, 60°C, and 90°C) and fermented for 14 days using a symbiotic culture of bacteria and yeast (SCOBY) and kombucha broth. Key parameters monitored included pH, total soluble solids (°Brix), reducing sugars, total phenolic content, and antioxidant activity. Each treatment was repeated three times, and the data was processed using simple statistical analysis. Results showed that all samples experienced a decrease in pH (from 3.95 to 3.3) and dissolved solids (by 3.23°Brix), alongside an increase in reducing sugars (from 0.02–0.05 mg/mL to 0.43–0.56 mg/mL), indicating active microbial fermentation. The 90°C extract exhibited the highest total phenolic content (823.82 μg GAE/mL) on day 2 and antioxidant activity (82.11%) on day 14, outperforming the 60°C and 30°C extracts. These results underscore the role of thermal extraction in enhancing the functional qualities of coffee ground kombucha and highlight its potential as a promising candidate for upcycled functional beverage development.